2019
DOI: 10.1002/ar.24196
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Fine Motor Capability on the Staircase Test Correlates with the Absolute Number, but Not the Density, of DARPP‐Positive Neurons in the Caudate‐Putamen

Abstract: Measurement of long-term functional and anatomical outcomes in the same animal is considered a powerful strategy for correlating structure with function. In a neonatal animal model of hypoxic-ischemic brain injury that is relevant to cerebral palsy, long-term functional deficits on the staircase test and long-term anatomical deficits in the absolute number of medium-spiny projection neurons in the caudate-putamen were reported in different animals due to logistical constraints. Here, we investigated if these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…58, the authors also confirmed the association between the reduced volume of the caudate nuclei and the impaired fine movement coordination in patients with hippocampal atrophy aged from 9 to 25 years of age. In addition, a neonatal animal study 59 demonstrated that the number of the medium-spiny projection neurons, the principal neurons which account for around 95% of all the neurons in the striatum, is significantly associated with the long-term fine motor capability on the staircase test. Taken together, the striatum should undertake key elements in the establishment of fine motor.…”
Section: Discussionmentioning
confidence: 99%
“…58, the authors also confirmed the association between the reduced volume of the caudate nuclei and the impaired fine movement coordination in patients with hippocampal atrophy aged from 9 to 25 years of age. In addition, a neonatal animal study 59 demonstrated that the number of the medium-spiny projection neurons, the principal neurons which account for around 95% of all the neurons in the striatum, is significantly associated with the long-term fine motor capability on the staircase test. Taken together, the striatum should undertake key elements in the establishment of fine motor.…”
Section: Discussionmentioning
confidence: 99%